Ecological Analysis of Children Tuberculosis (TB) in Indonesia - MP, Wahyu Ramadhan; Wijiastutik, Yuni (KHD-Production, 2024)
Tuberculosis (TB) in children is one of the causes of child mortality. Children and toddlers are very susceptible to exposure to tuberculosis germs, especially if there is a family that is confirmed to have Tuberculosis (TB) bacteriological notification. The purpose of this study was to analyze the poverty rate, active integrated healthcare center (Posyandu), and BCG Immunization related to Child TB Cases in Indonesia. The study design that was used is an ecological study approach (aggregate study) sourced from the 2019 Indonesian Health Profile data. Bivariate analysis was conducted using a scatter plot and Pearson correlation test. The results showed that the disparity in the percentage of Tuberculosis (TB) incidence in children was very high at 136.3% in West Java and the lowest in Aceh province at 9.6%. The results of the scatter plot and bivariate test showed that the greater the number of poverty rates, there is a tendency for the incidence of TB in children to be high, the more integrated healthcare center (Posyandu) active in an area, the higher the TB incidence in children, and the more children being immunized with BCG, the cases of Tuberculosis (TB) in children are also increasing. It was concluded that the poverty rate and active integrated healthcare center (Posyandu) had a positive relationship, while BCG immunization had a negative relationship with the incidence of Tuberculosis (TB) in children. It is recommended that the government develop special policies on target areas with the highest poverty rates and increase the activity of integrated healthcare center (Posyandu) in areas where the achievement of child Tuberculosis (TB) is still low, as well as increasing BCG immunization in areas with the most Tuberculosis (TB) cases in children to break the chain of transmission in the future.